2020
DOI: 10.1111/pcmr.12927
|View full text |Cite
|
Sign up to set email alerts
|

Current landscape of Oculocutaneous Albinism in Japan

Abstract: Oculocutaneous albinism (OCA), which is roughly divided into non‐syndromic and syndromic OCA, is a group of autosomal recessive disorders caused by mutations in genes associated with pigmentation. Patients with OCA have hypopigmentation and ocular manifestations such as photophobia, amblyopia, and nystagmus. Hermansky–Pudlak syndrome (HPS), the most common syndromic OCA, is characterized by the additional features of a bleeding tendency and other critical systemic comorbidities such as pulmonary fibrosis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 104 publications
0
9
0
4
Order By: Relevance
“…Oculocutaneous albinism type 4 (OCA4) is the most common type of albinism in Japan (Inagaki et al., 2004; Okamura & Suzuki, 2021) but rare (1:100,000) in the rest of the world. OCA4 is caused by mutations in the SLC45A2 gene (Newton et al., 2001).…”
Section: Oculocutaneous Albinism Typementioning
confidence: 99%
See 2 more Smart Citations
“…Oculocutaneous albinism type 4 (OCA4) is the most common type of albinism in Japan (Inagaki et al., 2004; Okamura & Suzuki, 2021) but rare (1:100,000) in the rest of the world. OCA4 is caused by mutations in the SLC45A2 gene (Newton et al., 2001).…”
Section: Oculocutaneous Albinism Typementioning
confidence: 99%
“…Recently, a review article reported the genetic analyses of 190 individuals or their family members who were clinically suspected OCA in Japan from 2007 to 2019 (Okamura & Suzuki, 2021). Among them, 54.7% of individuals (104 out of 190) were diagnosed as non‐syndromic OCA, while 21.6% (41 out of 190) were syndromic OCA.…”
Section: Overview Of Hps Patients In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the skin, hair, and eyes, or sometimes only the eyes, are affected [ 16 ]. There are four main types of OCA-OCA1 (TYR), OCA2 (OCA2), OCA3 (TRP1), and OCA4 (SLC45A2) [ 67 ]. In addition, albinism is observed as a symptom of various genetic diseases.…”
Section: Pigmentation Abnormality In Skin Diseasementioning
confidence: 99%
“…A variety of exon‐targeted sequencing approaches have been critical in identifying OCA variant alleles in diverse populations. However, 10%–25% of OCA individuals remain without a definitive, biallelic diagnosis (Grønskov et al, 2019; Kruijt et al, 2018; Lasseaux et al, 2018; Okamura & Suzuki, 2020; Simeonov et al, 2013; Wei et al, 2010; Zhong et al, 2019). Included in this subset are many individuals for whom only one deleterious allele is identified.…”
Section: Introductionmentioning
confidence: 99%